2023
DOI: 10.3389/fcimb.2023.1196967
|View full text |Cite
|
Sign up to set email alerts
|

Advances in gut microbiome in metabonomics perspective: based on bibliometrics methods and visualization analysis

Abstract: Background and aimsGastrointestinal microbial metabolomics is closely related to the state of the organism and has significant interaction with the pathogenesis of many diseases. Based on the publications in Web of Science Core Collection(WoSCC) from 2004 to 2022, this study conducted a bibliometric analysis of this field, aiming to understand its development trend and frontier, and provide basic information and potential points for in-depth exploration of this field.MethodsAll articles on gastrointestinal flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 124 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…In the same way, this software was also used to analyse the co‐citation of authors and the co‐occurrence of all keywords to explore the collaboration of authors and hotspots in this field. The acquisition of the total link strength which digitizes the strength of the connection is also one of the functions of VOSviewer 19 . Microsoft Excel (2016) was applied to display the map of publications over time and citations over time.…”
Section: Methodsmentioning
confidence: 99%
“…In the same way, this software was also used to analyse the co‐citation of authors and the co‐occurrence of all keywords to explore the collaboration of authors and hotspots in this field. The acquisition of the total link strength which digitizes the strength of the connection is also one of the functions of VOSviewer 19 . Microsoft Excel (2016) was applied to display the map of publications over time and citations over time.…”
Section: Methodsmentioning
confidence: 99%
“…By analyzing the literature citation count, we can identify research hotspots and cutting-edge fields that have garnered widespread attention and citation in the academic community ( Wang J. et al, 2023 ). The 11 clusters identified from the literature citations cover areas such as traditional Chinese medicine, tumor immunology, and clinical trials, indicating that this field has attracted extensive attention from interdisciplinary scholars.…”
Section: Current Research Landscape and Prevailing Issuesmentioning
confidence: 99%
“…It has been suggested that the number of human cells in the human body may be fewer than its microbial cells and that the number of human genes may be 10–100 times less than what is found in the intestine of the host [ 1 , 7 , 8 , 9 ]. In the last few decades, the amount of research conducted on the influence of the gut microbiome on the host organism, in a field called microbiomics, has increased significantly [ 10 , 11 , 12 ]. A new theory about the microbiome being a human “organ” gave impetus to investigating mechanisms of interactions between bacterial communities and other organism systems.…”
Section: Introductionmentioning
confidence: 99%